The Ebb and Flow of the Ghūrid Empire - Thomas, David C. (Adapa Monographs., 2018)
"The iconic minaret of Jām stands in a remote mountain valley in central Afghanistan, the finest surviving monument of the enigmatic 12th-century Ghūrid dynasty. The rediscovery of the minaret half a century ago prompted renewed interest in the Ghūrids, and this has intensified since their summer capital at Jām became Afghanistan?s first World Heritage site in 2002. Two seasons of archaeological fieldwork at Jām, the detailed analysis of satellite images, and the innovative use of Google Earth as a cultural heritage management tool have resulted in a wealth of new information about known Ghūrid sites, and the identification of hundreds of previously undocumented archaeological sites across Afghanistan. Drawing inspiration from the Annales school and the concept of an 'archipelagic landscape', David Thomas uses these data to re-assess the Ghūrids, giving us a more nuanced understanding of this significant Early Islamic polity." -- Back cover.